METHODS OF TEACHING FUTURE COMPUTER SCIENCE TEACHERS OBJECT-ORIENTED PROGRAMMING USING INFOGRAPHICS - Bekezhanova А.А.; Kurmanbekkyzy Н. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article considers the methods of teaching future teachers of computer science in object-oriented programming using infographics and their influence on the formation of subject competence. This approach is becoming more and more popular because infographics is an effective tool for visual presentation of information. The main objectives of the research were to study the effectiveness of infographics application in teaching future teachers of computer science in object-oriented programming. At the same time, the main attention was focused on the formation of subject matter competence of future teachers of computer science in object-oriented programming. The authors of this article present the results of a study conducted on a group of student future computer science teachers. Participants were taught using methods in which infographics were used to explain key concepts and principles of object-oriented programming. The study found that the use of infographics promotes better learning among student teachers and is an effective method for building subject matter competence. This approach contributes to a better understanding and application of the basic principles of object-oriented programming and can be useful in the development of curricula and methods of teaching computer science.